2009
DOI: 10.1530/eje-09-0398
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of increased lean muscle mass in women with polycystic ovary syndrome

Abstract: Objective: Muscle mass plays an important role in determining cardiovascular and metabolic risks in polycystic ovary syndrome (PCOS). In addition, whether lean mass influences carotid intima-media thickness (IMT) in PCOS has not been assessed. Design: Prospective investigation. Methods: Ninety-five women with PCOS were age-and weight-matched to 90 ovulatory controls. All women had dual X-ray absorptiometry for lean, fat and bone mass, and bone mass density (BMD). Serum testosterone, sex hormone-binding globuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
58
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 42 publications
10
58
2
1
Order By: Relevance
“…In turn, consistent with our results, a previous study has found that overweight/obese PCOS women presented increased lean mass as compared to normal controls [ 17 ] . In this sense, our patients with classic PCOS presented higher BMI than ovulatory PCOS and control women, refl ecting the great prevalence of overweight/obesity in PCOS -ranging from 30 to 70 % in diff erent populations [ 1 , 2 , 31 -34 ] .…”
supporting
confidence: 93%
See 1 more Smart Citation
“…In turn, consistent with our results, a previous study has found that overweight/obese PCOS women presented increased lean mass as compared to normal controls [ 17 ] . In this sense, our patients with classic PCOS presented higher BMI than ovulatory PCOS and control women, refl ecting the great prevalence of overweight/obesity in PCOS -ranging from 30 to 70 % in diff erent populations [ 1 , 2 , 31 -34 ] .…”
supporting
confidence: 93%
“…Obesity, especially central obesity, and insulin resistance were associated with this fi nding. While a few studies have analyzed lean body mass both in lean [ 5 , 15 ] and overweight/obese PCOS women [ 17 ] , this is the fi rst study comparing lean mass in diff erent PCOS phenotypes.…”
mentioning
confidence: 99%
“…Studies of lean body mass in PCOS women were also fraught with different results: (1) Carmina et al(2009) demonstrated that muscle mass increased in PCOS women compared to weight-matched controls (mean BMI of 27.6±5.8 kg/m²). The lean mass expressed as total lean mass divided by height was significantly higher in PCOS women with PCOS than in controls at 275 vs. 256 total g/height cm, p<0.01).…”
Section: Discussionmentioning
confidence: 99%
“…In keeping with experimental data, showing E 2 stimulates OPG production in human osteoblastic cells (38) our findings may reflect the anti-resorptive activity of E 2 /SHBG in bone metabolism in order to preserve bone mass. Controversy exists, nevertheless, as to whether or not increased bone mineral density is constantly found in PCOS (39,40). Furthermore, several factors such as androgen excess, insulin resistance, and increased fat mass may all intervene as potential determinants of bone mass in PCOS.…”
Section: Discussionmentioning
confidence: 99%